(untitled) - Ulla Connor (Cambridge, 1996)
This book presents a comprehensive view of the research in the field of contrastive rhetoric, emphasizing the connections between contrastive rhetoric and the related disciplines of composition studies, cultural anthropology, translation studies, and text linguistics
Keywords: contrastive linguistics,language and languages - study and teaching,rhetoric - study and teaching